Pengaruh Metode Bermain Peran Makro Terhadap Kemampuan Berpikir Simbolik Anak Kelompok B - Salsabila Arum Zahwa; Titin Faridatun Faridatun Nisa'; Yulias Wulani Fajar (PG-PAUD Trunojoyo, 2018)
This research aims to investigate the influence of macro role playing method on the children’s symbolic thinking ability at group B, TK Seruni Perumnas Kamal. Symbolic thinking is the ability to use symbols such as numbers, letters and images. This study was focused on examining macro role playing method to stimulate the children on the ability of using symbols. This research utilized quantitative approach by using experimental method with Pre-experimental research design in form of one-group pretest posttest. The subject of this study are 13 children at group B, TK Seruni Perumnas Kamal. Data were collected through observation and documentation. Then, data were analyzed by using wilcoxon level test. The result of data analysis was revealed that t count value is 0 and T table value 17, as 0 17, then Ha was accepted. Based on the data analysis, it shows there is a significant influence on macro role playing method on the children’s symbolic thinking ability at group B, TK Seruni Perumnas Kamal